Discrete event simulation of vessel stationkeeping operations in ice-rich waters. (July 2023) - Pearson, Wayne; Islam, Mohammed; Lau, Michael; Gash, Robert; Mills, Jason
This paper describes a high-fidelity numerical model that simulates vessel stationkeeping operations in ice-rich waters. The discrete event simulation engine incorporates several novel features, including new ice floe failure models for bow and midships locations; an ice floe creation strategy that facilitates rafting of ice floes; and a vessel thruster model that takes into account physical limitations such as thruster angle slew rates and propeller ramp rates. It accommodates a wide range of ice field specifications and runs in real-time on a standard desktop personal computer (Intel ® Core™ i7 Processor or equivalent). The model has been validated using physical measurements of a generic drillship model in several broken ice conditions; it predicted thruster forces and motions that were comparable to those observed during dynamic positioning operations.